Elgin Watch Building, New York World's Fair, Situated just inside World's Fair Boulevard gate - adjacent to bridge leading to Amusement Section (Curt Teich & Co.)
Features of the Elgin Watch Building at the New York World's Fair include a fully equipped astronomical observatory and watch museum. There's an exhibit of technical achievements in watch-making. America's most modern watches are also displayed.